The computer database for nurse anesthesia education programs. - Horton BJ; Revak GR; Jordan LM (AANA Journal, 1994)
Closures of nurse anesthesia educational programs and a resulting shortage of nurse anesthetists were the focus of a study by the National Commission on Nurse Anesthesia Education. This study occurred simultaneously with the implementation of an accreditation requirement for the submission of Annual Reports by the Council on Accreditation of Nurse Anesthesia Educational Programs (COA). Both groups recognized a need for routine collection of information about educational programs and the result was a cooperative effort between the AANA Education and Research Department and the COA to establish a computer database for public purposes. This article reviews the need for information, describes the Annual Report, and explains the functions and creation of the database.